Environmental risk factors in inflammatory bowel disease: a population-based case-control study in Asia-Pacific. Issue 7 (12th September 2014) - Ng, Siew C; Tang, Whitney; Leong, Rupert W; Chen, Minhu; Ko, Yanna; Studd, Corrie; Niewiadomski, Ola; Bell, Sally; Kamm, Michael A; de Silva, H J; Kasturiratne, Anuradhani; Senanayake, Yasith Udara; et al.
Abstract : Objective: The rising incidence of inflammatory bowel disease in Asia supports the importance of environmental risk factors in disease aetiology. This prospective population-based case-control study in Asia-Pacific examined risk factors prior to patients developing IBD. Design: 442 incident cases (186 Crohn's disease (CD); 256 UC; 374 Asians) diagnosed between 2011 and 2013 from eight countries in Asia and Australia and 940 controls (frequency-matched by sex, age and geographical location; 789 Asians) completed an environmental factor questionnaire at diagnosis. Unconditional logistic regression models were used to estimate adjusted ORs (aOR) and 95% CIs. Results: In multivariate model, being breast fed >12 months (aOR 0.10; 95% CI 0.04 to 0.30), antibiotic use (aOR 0.19; 0.07 to 0.52), having dogs (aOR 0.54; 0.35 to 0.83), daily tea consumption (aOR 0.62; 0.43 to 0.91) and daily physical activity (aOR 0.58; 0.35 to 0.96) decreased the odds for CD in Asians. In UC, being breast fed >12 months (aOR 0.16; 0.08 to 0.31), antibiotic use (aOR 0.48; 0.27 to 0.87), daily tea (aOR 0.63; 0.46 to 0.86) or coffee consumption (aOR 0.51; 0.36 to 0.72), presence of hot water tap (aOR 0.65; 0.46 to 0.91) and flush toilet in childhood (aOR 0.71; 0.51 to 0.98) were protective for UC development whereas ex-smoking (aOR 2.02; 1.22 to 3.35) increased the risk of UC. Conclusions: This first population-based study of IBD risk factors in Asia-Pacific supports the importance of childhood immunological, hygiene and dietary factors in the development of IBD, suggesting that markers of altered intestinal microbiota may modulate risk of IBD later in life.